2006
DOI: 10.1194/jlr.m600020-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipid synthesis through activation of AMP kinase: an additional mechanism for the hypolipidemic effects of berberine

Abstract: The alkaloid drug berberine (BBR) was recently described to decrease plasma cholesterol and triglycerides (TGs) in hypercholesterolemic patients by increasing expression of the hepatic low density lipoprotein receptor (LDLR). Using HepG2 human hepatoma cells, we found that BBR inhibits cholesterol and TG synthesis in a similar manner to the AMP-activated protein kinase (AMPK) activator 5-aminoimidazole-4-carboxamide 1-b-ribofuranoside (AICAR). Significant increases in AMPK phosphorylation and AMPK activity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
197
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(229 citation statements)
references
References 28 publications
18
197
2
2
Order By: Relevance
“…Intraperitoneal administration of BBR into obese db/db mice reduced body weight without a significant effect on food intake ( Fig. 1, A and B), which is consistent with previous reports (5,9,16,19,38). In addition, we observed that BBR lowered the RQ ratio and increased energy expenditure (Fig.…”
Section: Bbr Alleviates Dyslipidemia and Fatty Liver In Obese Micesupporting
confidence: 81%
See 1 more Smart Citation
“…Intraperitoneal administration of BBR into obese db/db mice reduced body weight without a significant effect on food intake ( Fig. 1, A and B), which is consistent with previous reports (5,9,16,19,38). In addition, we observed that BBR lowered the RQ ratio and increased energy expenditure (Fig.…”
Section: Bbr Alleviates Dyslipidemia and Fatty Liver In Obese Micesupporting
confidence: 81%
“…We and others (9,19,38) have reported that BBR reduces body weight, causes a significant improvement in glucose tolerance, and improves insulin action in obese and/or diabetic subjects by activating AMPK. A large body of evidence indicates that BBR enhances insulin sensitivity and reduces hyperlipidemia (5,9,16,38). Thus it is plausible to speculate that this mechanism might be applied therapeutically to treat fatty liver and hyperlipidemia.…”
mentioning
confidence: 99%
“…Reductions of plasma TAG by BBR were also observed in other studies in rats with diabetes and nephritis [42,43,47]. Results from several in vitro studies have demonstrated that BBR decreases TAG levels through regulating fatty acid metabolism toward the downregulation of adipogenesis [51][52][53]. BBR upregulates the phosphorylation of the AMPactivated protein kinase (AMPK), which phosphorylates and inactivates acetyl-CoA carboxylase (ACC) [51,52].…”
Section: Discussionmentioning
confidence: 62%
“…Results from several in vitro studies have demonstrated that BBR decreases TAG levels through regulating fatty acid metabolism toward the downregulation of adipogenesis [51][52][53]. BBR upregulates the phosphorylation of the AMPactivated protein kinase (AMPK), which phosphorylates and inactivates acetyl-CoA carboxylase (ACC) [51,52]. The inactivation of ACC results in the inhibition of fatty acid synthesis but the enhancement of fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Acute activation of AMPK has been shown to result in the phosphorylation and inactivation of acetyl-CoA carboxylase, a key enzyme regulating the balance between fatty acid biosynthesis and oxidation [13,48]. Inactivation of acetyl-CoA carboxylase leads to a decrease in fatty acid synthesis and a concomitant increase in fatty acid oxidation, resulting in depletion of IMTG stores [49,50].…”
Section: Discussionmentioning
confidence: 99%